Utilização de resíduos da indústria de calçados em blocos de vedação com novas geometrias - Bloco Evang - Pimentel, Ubiratan Henrique Oliveira (2005)
The generation of residues by the footwear s industry, especially E.V.A. residues (Ethilene Vinil Acetate), is calling specialist s attention for the elaboration of researches that make possible to recycle these residues for the Civil Construction Industry. It is known that such residues have as characteristics: low specific mass, good acoustic and thermal behavior, stability, inert, not susceptible to fungi, besides having good potential to be used as a of synthetic attaché for elaboration of light composites, being a substitute for part of the natural aggregates. This work presents results of a research about the use of these residues as a light aggregate for the fabrication of masonry blocks designated to the Civil Construction, using an alternative material and a new geometry (EVANG Block). The objective was to develop a new masonry block with increased dimensions, if compared to the traditional sizes, to be used as an alternative masonry reusing industrial residues, preserving the environment, considering its characteristics and the manual process of manufacture with a steel mold specified at the experiments. The results show that the block, with dimensions of 59,0 cm x 26,5 cm x 11,5 cm (determined by a modulated pattern of construction), is highly flexible with an average strength of 0,82 MPa, using 80% of residues on its composition to replace the natural aggregates. Therefore, it may be told that there are important contributions in this research, showing its technical viability: the possibility to recycle an industrial residue, the reduction of the need of natural aggregates and the increase of productivity for the masonry walls at the buildings